ULASAN: KEBERHASILAN BELAJAR SISWA MELALUI PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STAD - Murtihapsari Murtihapsari; Sri N Patandean; Radite Yogaswara (Chemistry Education Department of Education and Teaching Faculty, 2021)
One way learning method could lead students unfocused and difficult to gain learning outcomes . Currently, the Comparative learning model by Student Team Achievement Division (STAD) it is largely used in teaching. Therefore, this review was made to understand and find out the impact of the learning model system in the class. The study is based on literatures with the following criteria (1) STAD cooperative type with a quasi-experiment and (2) research subjects were at the senior high school at MIPA class. We obtained 14 articles are similar with the criteria. Each of the article shortly describe the research finding. Indicator of student success with cooperative type STAD can be seen from the average value above 50%. It was found that the STAD type of cooperative learning model lead the creation of actively students mood, creative, and independent learning atmosphere for students in receiving, processing, and answering learning material. This learning model is likely one of the most adaptive model learning, modifications some elements are required depend on characteristic and environment learning locally.